Biological Activity Investigation of Phytocomponents in Mangosteen (Garcinia mangostana L.): In Silico Study - Arif Nur Muhammad Ansori1 , Raden Joko Kuncoroningrat Susilo2 , Suhailah Hayaza2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Indonesia has abundant medicinal plants, which have been historically used by the population in treatingdiseases for generations. Traditional Indonesian medicine and the medicinal plants used could lead to thediscovery of novel drugs. The mangosteen or Garcinia mangostana L. is a well-known medicinal plantthat has been used to treat various diseases worldwide. The pharmacological activities and phytochemicalcomposition of the whole plant of mangosteen have been investigated and identified by scientists in recentdecades. Therefore, this study aims to generate the prediction of the biological activity of phytocompotentsin mangosteen. In this study, we extracted 18 phyocomponents of mangosteen from PubChem, an openchemistry database at the National Institutes of Health (NIH), USA. Then, we predicted the pharmacokineticproperties and druglike nature of the phytocomponents using the SwissADME web server, Swiss Instituteof Bioinformatics, Swiss. Furthermore, PASS (Prediction of Activity Spectra for Substances) web resourcehas been employed as a strong potential tool to predict the biological activity. In summary, we revealed thebiological activity of 18 phytocomponents of the mangosteen. However, further trials, such as in vitro andin vivo evaluation, are needed to prove the validity of these findings.